An active metabolite of oltipraz (M2) increases mitochondrial fuel oxidation and inhibits lipogenesis in the liver by dually activating AMPK. (12th March 2013) - Kim, Tae Hyun; Eom, Jeong Sik; Lee, Chan Gyu; Yang, Yoon Mee; Lee, Yong Sup; Kim, Sang Geon
<x xml:space="preserve">Abstract</x> Background and Purpose Oltipraz, a cancer chemopreventive agent, has an anti‐steatotic effect via liver X receptor‐α (LXRα) inhibition. Here we have assessed the biological activity of a major metabolite of oltipraz (M2) against liver steatosis and steatohepatitis and the underlying mechanism(s). Experimental Approach Blood biochemistry and histopathology were assessed in high‐fat diet (HFD)‐fed mice treated with M2. An in vitroHepG2 cell model was used to study the mechanism of action. Immunoblotting, real‐time PCR and luciferase reporter assays were performed to measure target protein or gene expression levels. Key Results M2 treatment inhibited HFD‐induced steatohepatitis and diminished oxidative stress in liver. It increased expression of genes encoding proteins involved in mitochondrial fuel oxidation. Mitochondrial DNA content and oxygen consumption rate were enhanced. Moreover, M2 treatment repressed activity of LXRα and induction of its target genes, indicating anti‐lipogenic effects. M2 activated AMP‐activated protein kinase (AMPK). Inhibition of AMPK by over‐expression of dominant negative AMPK (DN‐AMPK) or by Compound C prevented M2 from inducing genes for fatty acid oxidation and repressed sterol regulatory element binding protein‐1c (SREBP‐1c) expression. M2 activated liver kinase B1 (LKB1) and increased the AMP/ATP ratio. LKB1 knockdown failed to reverse target protein modulations or AMPK activation by M2, supporting the proposal that both LKB1 and increased AMP/ATP ratio contribute to its anti‐steatotic effect. Conclusion and Implications M2 inhibited liver steatosis and steatohepatitis by enhancing mitochondrial fuel oxidation and inhibiting lipogenesis. These effects reflected activation of AMPK elicited by increases in LKB1 activity and AMP/ATP ratio.